BMI1 Drives Steroidogenesis Through Epigenetically Repressing the p38 MAPK Pathway - Yu, Jun; Wu, Yibo; Li, Hong; Zhou, Hui; Shen, Cong; Gao, Tingting; Lin, Meng; Dai, Xiuliang; Ou, Jian; Liu, Meiling; Huang, Xiaoyan; Zheng, Bo; et al. (Frontiers in Cell and Developmental Biology, 2021)
Testosterone biosynthesis progressively decreases in aging males primarily as a result of functional changes to Leydig cells. Despite this, the mechanisms underlying steroidogenesis remain largely unclear. Using gene knock-out approaches, we and others have recently identified Bmi1 as an anti-aging gene. Herein, we investigate the role of BMI1 in steroidogenesis using mouse MLTC-1 and primary Leydig cells. We show that BMI1 can positively regulate testosterone production. Mechanistically, in addition to its known role in antioxidant activity, we also report that p38 mitogen-activated protein kinase (MAPK) signaling is activated, and testosterone levels reduced, in BMI1-deficient cells; however, the silencing of the p38 MAPK pathway restores testosterone production. Furthermore, we reveal that BMI1 directly binds to the promoter region of Map3k3, an upstream activator of p38, thereby modulating its chromatin status and repressing its expression. Consequently, this results in the inhibition of the p38 MAPK pathway and the promotion of steroidogenesis. Our study uncovered a novel epigenetic mechanism in steroidogenesis involving BMI1-mediated gene silencing and provides potential therapeutic targets for the treatment of hypogonadism.